(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Cancer is the second leading causes of mortality across the planet which has had affected millions. In spite of massive efforts in producing new molecules and chemotherapeutic approaches for managing cancer, it continued to be the global threat. Small hybrid molecules have gained popularity in chemotherapy due to their potential and smart characteristics in modulating biological targets. The present research attempts in developing few novel hybridized derivatives of murrayanine (an active carbazole derivative) by the semi-synthetic approach to form substituted thiazole linked murrayanine-Schiff’s base derivatives. The protocol involved murrayanine 1 as the template material for constructing a hybridized Schiff’s base intermediate 3, which further by Hantzch’s cyclization was subsequently converted to various hybridized thiazoles analogs 5a-5f. The purity of the synthesized compounds was ascertained by sophisticated analytical techniques. The anti-cancer potential was screened against breast cancer cell lines; MCF-7 and MDA-MB-231 by Sulforhodamine B (SRB) assay. The compound 5b displayed most potent anti-proliferative activity with IC50 values of 23.41μM against MCF-7 cell line and 32.15μM against MDA-MB-231 cell line. It has been observed that analogs having electron withdrawing substituents exhibited pronounced anticancer activity. The docking study was performed by Autodock Vina where the results were found to be in full agreement with the cytotoxic study, depicting that the probable cytotoxic outcome by EGFR inhibitory mechanism. The study revealed the potential of novel hybridized derivatives as active anti-breast cancer candidates. The research will encourage (medicinal) chemists in rationally designing of semi-synthetic analogs of a heterocyclic prototype having pronounced anti-cancer activity.